2015
DOI: 10.13189/aeb.2015.031002
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Cigarettes in Tanzania and Implications for Tobacco Taxation Policy

Abstract: The study attempts to estimate the demand for cigarettes in Tanzania and presents simulation results on the effect of the cigarette excise tax on smoking participation, government revenue, and related topics. After briefly summarizing the magnitude and spread of cigarette consumption in the country, the paper reviews some empirical estimates from African and other countries. The 2008 Tanzanian household budget survey was used to estimate the demand for cigarettes in Tanzania. The descriptive statistics suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Studies from multiple Sub-Saharan African countries [11], as well as specific-country studies, including from South Africa [12], Tanzania [13], Uganda [14], and Zambia [15], have confirmed that higher cigarette prices reduced smoking prevalence and intensity of use. Previous international research has found that youth are even more price-responsive than adults [16], making tobacco taxation particularly effective in countries with high population growth, where measures aimed at youth smoking are especially needed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from multiple Sub-Saharan African countries [11], as well as specific-country studies, including from South Africa [12], Tanzania [13], Uganda [14], and Zambia [15], have confirmed that higher cigarette prices reduced smoking prevalence and intensity of use. Previous international research has found that youth are even more price-responsive than adults [16], making tobacco taxation particularly effective in countries with high population growth, where measures aimed at youth smoking are especially needed.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation analysis based on a two-part demand equation model developed by Kidane et al (2015) and Kidane et al (2017) shows the impacts of the excise duty hike for cigarettes on households' consumption and government revenue. The study found that, prior to raising the excise duty on cigarettes, the smoking prevalence was 15.95 per cent and per capitа consumption was 1.33 cigarettes per day, implying 24.27 packs per year.…”
Section: Indirect Benefits Of Tax On Tobacco Productsmentioning
confidence: 99%
“…They used Autoregressive Distributed Lag (ARDL) model and showed that education, income level, and the price of the cigarette is insignificant on cigarette consumption while the life expectancy at birth has a significantly negative impact on cigarette consumption. By employing household survey data and utilizing the two-stage least square model, Kidane et al (15) found that the effect of the price changes is significantly negative in all income groups in Tanzania. They also demonstrated that age and education level are other significant factors explaining cigarette consumption.…”
Section: E a R L Y A C C E S Smentioning
confidence: 99%